Lichen scrofulosorum: An important marker of occult tuberculosis - Dogra Naina; Shah Shazia; Dogra Devraj (Wolters Kluwer Medknow Publications, 2008)
Lichen scrofulosorum is a tuberculid that is usually seen in children or young adults. Although a rare occurrence, this tuberculid is an important marker of occult tuberculosis, which may not be detected otherwise. We report here a case of lichen scrofulosorum in a ten year-old boy with typical grouped lichenoid papules on the trunk associated with axillary tuberculous lymphadenitis.